Affective profiles in Italian high school students: life satisfaction, psychological well-being, self-esteem, and optimism - Di Fabio, Annamaria; Bucci, Ornella (Frontiers in Psychology, 2015)
The affective profiles model distinguishes between individuals who are self-fulfilling (high positive affect, low negative affect), high affective (high positive affect, high negative affect), low affective (low positive affect, low negative affect), and self-destructive (low positive affect, high negative affect). The literature shows that the affective profiles model has been used with Swedish people in particular in order to determine differences among profiles in relation to life satisfaction, psychological well-being, self-esteem, and optimism. The present research investigated these differences in Italian high school students. Two studies were conducted: the first with 156 Italian high school students and the second with 148 Italian high school students. The first study analyzed differences among affective profiles with regard to life satisfaction and psychological well-being while the second study analyzed differences among affective profiles with regard to self-esteem and optimism. In the first study, the Positive and Negative Affect Schedule (PANAS), the Satisfaction With Life Scale (SWLS), and the Meaningful Life Measure (MLM) were administered to the participants. In the second study, the Positive and Negative Affect Schedule (PANAS), the Self-Esteem Scale (SES), the Life Orientation Test - revised (LOT-r) were administered to the participants. The results of the first study showed that, with respect to the other profiles, the self-fulfilling participants had greater life satisfaction and psychological well-being. The results of the second study showed that, with respect to the other profiles, the self-fulfilling participants had higher self-esteem and optimism. These results revealed differences among affective profiles regarding life satisfaction, psychological well-being, self-esteem, and optimism in the Italian context as well thereby offering new possibilities for cross-cultural research and for enhancing self-fulfilling profiles.